Prototype for multidisciplinary research in the context of the Internet of Things - López-Benítez, Miguel; Drysdale, Timothy D.; Hadfield, Simon; Maricar, Mohamed Ismaeel (Elsevier, 2017)
The Internet of Things (IoT) poses important challenges requiring multidisciplinary solutions that take into account the potential mutual effects and interactions among the different dimensions of future IoT systems. A suitable platform is required for an accurate and realistic evaluation of such solutions. This paper presents a prototype developed in the context of the EPSRC/eFutures-funded project “Internet of Surprise: Self-Organising Data”. The prototype has been designed to effectively enable the joint evaluation and optimisation of multidisciplinary aspects of IoT systems, including aspects related with hardware design, communications and data processing. This paper provides a comprehensive description, discussing design and implementation details that may be helpful to other researchers and engineers in the development of similar tools. Examples illustrating the potentials and capabilities are presented as well. The developed prototype is a versatile tool that can be used for proof-of-concept, validation and cross-layer optimisation of multidisciplinary solutions for future IoT deployments.